Development of the inner ear and regeneration of hair cells after hearing impairment - Xin Bing; Chengcheng Liu; Xue Cao; Chengzhilin Li; Xiaochen Gao; Fangyuan Zhu; Xinhao Wu; Na Guo; Houyang Hu; Ming Xia; Miaoqing Zhao (Fundamental Research)
Hearing loss, as a sensory disorder, is the most common occurrence among humans, which has received increasing attention from society. It is mainly caused by the damage of inner ear hair cells (HCs) or the degeneration of spiral ganglion neurons. In mammals, cochlear HCs cannot regenerate naturally after injury, leading to irreversible hearing loss. Therefore, HCs are essential for hearing protection. In recent years, the protection of drug-related ototoxicity, inner ear stem cells, gene therapy, new materials, and signal regulation have become important ways to develop regeneration strategies of HCs. An in-depth study of the causes of the occurrence and development of hearing impairment and the regeneration of hearing loss for effective prevention, discovery, and treatment of deafness has great significance. This review aimed to analyze the development of the inner ear and summarize the related factors leading to HCs injury and the research progress of regeneration after injury.